Estrutura de compras governamentais do DF: análise comparativa entre centralização e descentralização - Silva, Rita Luiza de Aquino da (2025)
This study examines and compares centralized and decentralized public procurement models within the Government of the Federal District (GDF), with a focus on cost efficiency, process agility, and operational simplification. Consequently, government procurement should be strategically employed not only to secure costeffective solutions but also to promote socioeconomic development through evidencebased management and long-term planning—all while preserving transparency, speed, and service quality. To achieve this objective, the research employs a comparative analysis of crystal sugar procurement, utilizing historical data from multiple fiscal periods to evaluate how each model affects contracting timelines and associated expenditures. The study further investigates the influence of organizational frameworks on procurement outcomes. Despite its low unit cost, crystal sugar represents a substantial share of public spending, demanding meticulous oversight. This commodity was selected due to its standardized use across government agencies, enabling a precise comparison between procurement systems. The centralized model necessitates a unified strategy, where a single coordinating body oversees all acquisitions to optimize economies of scale and procedural control. In contrast, decentralized procurement may offer greater adaptability to agency-specific requirements, fostering localized decision-making. By providing empirical insights into public sector governance, this study contributes to policy discussions on procurement reform within the GDF. Its findings are designed to support administrative innovations that enhance resource allocation, ultimately benefiting both public institutions and the citizens they serve. As such, this research represents a strategic instrument for advancing public management excellence.